Core body temperature evaluation: Suitability of measurement procedures - Emília Quelhas Costa (2012)
Infrared Core body temperature (Tc) is regulated to achieve the homeostatic balance between production and dissipation of heat. This parameter is one of the most important factors to monitor and study the regulation of human temperature. It helps at studying the cognitive response to high temperatures' exposure and it is one of the best physiological indicators used to avoid heat injuries in different activities independently from individual characteristics such as: age, height, body weight or body fat. It has also been used in several studies, both in the laboratory and in the real work context, including athletes, students, and military forces. The main goal of this study was to select the most suitable method and equipment for measuring core temperature in occupational environment. This study was based on literature review from large databases and scientific journals. The literature reviewed confirmed that the gold standard methods for Tc measuring (rectal and esophageal) have some advantages but also limitations, especially due to discomfort caused by sensors implantation. Alternatively, it is possible to use thermal ingestible sensors without the limitations of the other methods. This technique was applied, tested and validated by several researchers and approved by the ethic committees. However, there are still doubts about the scope of its applicability. According to all the information collected, it was concluded that the most suitable procedure to measure core temperature in occupational activities is the TIS. For this reason, the authors believe that the intraabdominal temperature measurement with TIS is, from the available methods, the most suitable for the measurement of Tc in the workplace. The method was, therefore, selected for further research.